Physiological analysis of severe chlamydia psittaci pneumonia and clinical diagnosis after doxycycline-based treatment - He, Lujuan; Yang, Hongzhong; Liu, Shenggang; Liang, Weijun; Zhou, Zezhi; Long, Jing; Wu, Jinyang (Frontiers in Physiology, 2023)
Objective: To describe the clinical spectrum of severe Chlamydia psittaci pneumonia in order to understand the disease better. Methods: Retrospective analysis was made on 22 patients with severe Chlamydia psittaci pneumonia diagnosed in ICU by next-generation sequencing of metagenome (NGS) from January 2019 to August 2022, including clinical characteristics, laboratory examination results, imaging characteristics, treatment, and prognosis. Results: We included 22 patients with severe Chlamydia psittaci pneumonia, 12 of whom had a history of virus exposure. There were 9 cases with multiple bacterial infections, and the common symptoms included fever (22/22100%), dyspnea (22/22100%), cough (16/22,72.7%), and myalgia (14/22,63.6%). Laboratory data showed that white blood cells were average or slightly increased, but the levels of C-reactive protein and neutrophils were high. CT findings of the lung were consolidation (13/22, 59.1%) and pleural effusion (11/22, 50%). Only one lobe was involved in 11 patients (50%). Before diagnosis, 18 patients (81.8%) did not have atypical pathogens in their antimicrobial regimen. After diagnosis, 14 patients (63.6%) received single drug treatment, of which doxycycline or moxifloxacin were the most commonly used drugs. Among 22 patients, two died, four improved, and 16 were cured. Conclusion: The clinical manifestations of severe Chlamydia psittaci pneumonia are nonspecific. The application of NGS can improve the diagnostic accuracy of psittaci fever, reduce the unnecessary use of antibiotics, and shorten the course of the disease. Doxycycline-based treatment is effective for severe chlamydia psittaci pneumonia, but it is necessary to understand the secondary bacterial infection and other complications in the course of the disease.